2021
DOI: 10.1097/ajp.0000000000000934
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Noninvasive Brain Stimulation to Reduce Nonspecific Low Back Pain

Abstract: Objective: We conducted a systematic review/meta-analysis to evaluate noninvasive brain stimulation (NIBS) efficacy to alleviate pain and improve disability in low back pain (LBP). Materials and Methods:A systematic literature search was performed by a librarian in MEDLINE, Embase, EBM Reviews, CINAHL, and Web of Science databases (last search: January 14, 2021). Data were pooled by the number of sessions and follow-up periods. Independent reviewers performed screening, data extraction, and risk of bias. Pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…To date, there are only a limited number of studies evaluating the TES interventions in people with CLBP 45 46. A recent meta-analysis demonstrates that there is moderate quality evidence suggesting that neither repeated sessions of non-invasive brain stimulation nor its combination with other treatments significantly improves pain or disability in people with CLBP 45.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, there are only a limited number of studies evaluating the TES interventions in people with CLBP 45 46. A recent meta-analysis demonstrates that there is moderate quality evidence suggesting that neither repeated sessions of non-invasive brain stimulation nor its combination with other treatments significantly improves pain or disability in people with CLBP 45.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only a limited number of studies evaluating the TES interventions in people with CLBP 45 46. A recent meta-analysis demonstrates that there is moderate quality evidence suggesting that neither repeated sessions of non-invasive brain stimulation nor its combination with other treatments significantly improves pain or disability in people with CLBP 45. As most studies evaluating tDCS of single brain region demonstrated little success in improving pain and disability in people with CLBP, future trials focusing on different TES techniques, targeting multiple cortical areas, using various parameters are warranted and recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, brain network disturbance is considered one of the possible causes of CLBP. A recent systematic analysis (eight studies) revealed that, compared with sham stimulation, 1 session of tDCS treatment resulted in substantial pain relief ( Patricio et al, 2021 ). By contrast, multiple sessions of tDCS treatment did not improve short-term and medium-term pain.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%